Surgical management of intraventricular hemorrhage and posthemorrhagic hydrocephalus in premature infants – single center experience - David Krahulik; Martin Wita; Vanda Volkova; Jan Halek; Jan Krahulik; Filip Blazek (Frontiers in Pediatrics)
IntroductionIntraventricular hemorrhage (IVH) is a severe complication of prematurity, often leading to posthemorrhagic hydrocephalus (PHH). While advances in neonatal care have reduced the incidence of IVH, managing progressive PHH remains challenging. Surgical interventions are crucial for reducing intracranial pressure and preventing long-term neurodevelopmental deficits. This study presents our single-center experience in the surgical management of IVH and PHH in premature infants, highlighting outcomes associated with different surgical strategies.MethodsThis retrospective study was conducted at a tertiary neonatal care center between 2017 and 2023. Premature infants (≤32 weeks of gestation or <1,500 g birth weight) were screened for IVH using cranial ultrasound. IVH was graded using the modified Papile classification. Clinical data, imaging findings, and surgical outcomes were collected. Temporizing measures included ventricular access devices (VAD), ventriculosubgaleal (VSG) shunts, and external ventricular drainage (EVD), with permanent ventriculoperitoneal (VP) shunts used for long-term management. Neurodevelopmental outcomes were evaluated at one-year follow-up.ResultsThe study included 402 premature infants, of whom 75 (18.7%) were diagnosed with IVH. Among these, 6 infants developed PHH requiring surgical intervention. VAD shunting was the preferred temporizing measure due to lower infection rates, with an average duration of 35 days before conversion to VP shunting in 4 children. At one-year follow-up, 64% of infants demonstrated no significant neurological impairment, while 23.2% had severe complications, including developmental delays or motor deficits. Mortality was 20.1%, primarily in infants with Grade III-IV IVH. Logistic regression analysis identified gestational age, corticosteroid treatment, and inborn status as significant predictors of favorable outcomes.ConclusionEffective surgical management of PHH in premature infants hinges on timely diagnosis, early intervention, and appropriate selection of temporizing measures. Ventricular access devices (VAD) offer a safe and effective strategy to stabilize infants before permanent shunt placement, minimizing complications and improving long-term outcomes. Close collaboration between neonatologists and neurosurgeons remains essential to optimizing care and reducing morbidity in this high-risk population.